Outbreak of vaccine-preventable diseases in Muslim majority countries - Ali Ahmed; Kah S. Lee; Allah Bukhsh; Yaser M. Al-Worafi; Md. Moklesur R. Sarker; Long C. Ming; Tahir M. Khan (Elsevier, 2018)
The increase in Muslim parents' refusal and hesitancy to accept childhood vaccination was identified as one of the contributing factors in the increase of vaccine-preventable diseases cases in countries such as Afghanistan, Malaysia and Pakistan. The spread of inaccurate and irresponsible information by the anti-vaccination movement may inflict more harm than good on Muslim communities. To curb this issue, health authorities in Pakistan and Malaysia have resorted to imposing strict punishments on parents who refuse to allow their children to be vaccinated. Information addressing religious concerns such as the halal issue must be made priority and communicated well to the general public, encouraging not only the acceptance of vaccinations but motivating communities to play an active role in promoting vaccination. Local government of the affected region need to work towards creating awareness among Muslim parents that vaccinations are a preventative public health strategy that has been practised and acknowledged by many doctors of all faiths. Keywords: Policy coherence, Hesitancy and refusal, Vaccine manufacturing, Halal, Developing countries